Analisis Hubungan Indeks Massa Tubuh dengan Daya Tahan Kardiorespirasi pada Anggota Komunitas Futsal Fakultas Kedokteran Universitas Lampung - Ekki Pirmansyah; Berawi, Khairun Nisa; Ramadhian, Muhammad Ricky (Medula, 2025)
Cardiorespiratory endurance is a key indicator of physical fitness, reflecting the efficiency of the heart, lungs, and circulatory system in transporting and utilizing oxygen. Low cardiorespiratory endurance can increase cardiac workload and blood pressure, ultimately elevating the risk of cardiovascular disease. In addition to cardiorespiratory endurance, body mass index (BMI) is another important measure of physical fitness. This study aimed to analyze the relationship between BMI and cardiorespiratory endurance among members of the Futsal Community of the Faculty of Medicine, University of Lampung. This analytic observational study employed a cross-sectional design. A total sampling technique was used, involving 62 student members of the futsal community. The independent variable was BMI, calculated as body weight (kg) divided by height squared (m²). The dependent variable was cardiorespiratory endurance, assessed using the Rockport test. Data were analyzed using the Chi-square test. In this study, most of the participants had a normal BMI (40.32%), while cardiorespiratory endurance levels were predominantly categorized as poor (38.71%) and fair (37.81%). Bivariate analysis yielded a p-value of 0.000, indicating a significant association between BMI and cardiorespiratory endurance among members of the Futsal Community of the Faculty of Medicine, University of Lampung. The direction of the correlation was negative, meaning that an increase in BMI was associated with a decrease in cardiorespiratory endurance.